Effect of Dredging Rate, Sintering Time, Cooling Media on Corrosion Results of Carbon Steel Dredging - dani irawan (International Journal of Science, Engineering, and Information Technology, 2021)
Metal reinforcement that has an impact on improving mechanical properties can occur in various ways, including by strain hardening mechanisms, solid solutions, second phase, prespitations, disperse, grain refinement and texture. In recent years, another method has been developed to obtain good mechanical properties without adding alloy elements, namely by the method of comprehensive plastic deformation (Severe Plastic Deformation). The purpose of this research is to conduct a study of rolling using medium carbon steel with a treatment temperature above recrystallization, rolling rate, sintering time, cooling media as an effort to develop and design new innovations about steel structures being rolled. The study of developing rolling techniques that can be applied in industry and can be applied as learning material / media in higher education requires structured research stages. The best impact value from this temper process is a temperature of 550 ° C for 1 hour where the impact value is 1.58 J / mm² with air conditioning media. In the rolling process above the recrystallization temperature 800 ° C deformation 20% the impact value is 1.7 J / mm² where the toughness indicates a ductile fracture while the deformation is 10% the impact value